Burnout assessment among academic dental staff during COVID‐19: Data from Arab countries. Issue 11 (3rd July 2022) - Alsaggaf, Arwa U.; Bustani, Mohammad; Abid, Mushriq; Hakeem, Faisal F.; Abed, Hassan
Abstract: Purpose/objective: This study aimed to identify factors that were associated with high burnout and investigate the prevalence of burnout among academic dental staff during the COVID‐19 pandemic. Method: A cross‐sectional online survey was carried out among academic dentists who are working in multiple dental schools in Arab countries. The Copenhagen Burnout Inventory was used to assess participants' work‐related burnout. Logistic regression was used to assess the factors that increase the risk of burnout among academic dentists. Results: Of the 254 participants who took part in the study, 141 were males (55.5%). The average age of the participants in the study was 42.1 years (standard deviation = 10.0). The prevalence of burnout among participants was 44.9% ( n  = 114). Using a fully adjusted logistic regression model, age (odds ratio [OR] = 1.05, 95% confidence interval [CI]: 1.01–1.09, p  = 0.008) and gender (OR = 0.54, 95% CI: 0.31–0.94, p  = 0.03) were significant variables associated with high overall burnout. Female individuals had a substantially reduced risk of experiencing high personal burnout than male participants (OR = 0.56, 95% CI: 0.32–0.98, p  = 0.043) in the personal burnout subdomain. While in the patient's burnout subdomain, age (OR = 1.04, 95% CI: 1.00–1.08, p  = 0.048), type of speciality (OR = 2.44, 95% CI: 1.02–5.83, p  = 0.044), and teaching place (OR = 2.49, 95% CI: 1.21–5.11, p  = 0.013) were associated with higher burnout. Conclusion: This study concluded that gender and age are characteristics that increase the risk of higher burnout among academic dentists during the COVID‐19 pandemic.